Changes in polyphenol composition and bioactivity of the native Chilean white strawberry (Fragaria chiloensis spp. chiloensis f. chiloensis) after in vitro gastrointestinal digestion. (March 2018) - Thomas-Valdés, Samanta; Theoduloz, Cristina; Jiménez-Aspee, Felipe; Burgos-Edwards, Alberto; Schmeda-Hirschmann, Guillermo
Abstract: The Chilean white strawberry ( Fragaria chiloensis spp. chiloensis f. chiloensis ) is a semi-domesticated strawberry with high polyphenol content and antioxidant activity occurring in southern Chile. The aim of this work was to compare the composition and bioactivity of the polyphenol-enriched fruit extract (PEE) before and after simulated gastrointestinal digestion (GID). Results show a decrease by > 50% in the total phenolic (TP) content at the end of the GID, compared to the non-digested PEE. A reduction in the antioxidant capacity of the PEEs was observed after GID by means of DPPH, FRAP, TEAC and anion superoxide assays. After simulated GID the PEE significantly inhibited α-glucosidase with an IC50 value of 3.13 μg/mL. The inhibition of pancreatic lipase was reduced by 95% after GID. All the PEEs did not show inhibitory effect towards α-amylase throughout the GID. In the same way, the PEEs did not significantly protect human gastric adenocarcinoma (AGS) cells against H2 O2 -induced stress. Thirty eight compounds were tentatively identified in the non-digested PEE. The compounds that were more affected by the simulated GID were simple phenolics. After the GID, only 33 and 25 compounds were detected, in the gastric and intestinal steps, respectively. These results evidence the changes elicited by GID on the bioactivity and polyphenolic composition of the white strawberry. Graphical abstract: Highlights: Effect of in vitro gastrointestinal digestion (GID) on white strawberry was studied. Changes in phenolic profiles and bioactivity before and after GID were assessed. A decrease in the content of simple phenolic acids after GID was observed. A reduction in the antioxidant effect and bioactivity after GID was observed. The activity towards metabolic syndrome-associated enzymes decreased after GID.